Easy-Apply Laporan Keuangan Berbasis Android For Free: UMKM Melek Digital - Muhammad Qomaruddin Ridwan; Anggraeni Yunita; Fitri Ramdhani Harahap (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
This community service activity aims to work up MSME in record and prepare financial reports using an Android-based application. This activity is based on the fact that MSME have made a large economic contribution to the development and economic resilience of society, but they still face many stugles. There are still many MSMEs that have not prepared adequate financial reports, which has an impact on limited access to capital, thereby hampering the development of MSME business capacity. In fact, currently there are many free Android-based applications available to help MSMEs prepare financial reports. MSME players can use this application to record finances and then the application will prepare financial reports automatically. Apart from functioning as a performance measurement tool, financial reports will also increase MSMEs' access to capital. This community service activity was carried out in Sungkap Village, Central Bangka Regency with participants being business actors who are members of the Dharma Wanita Business Group of Sungkap Village. The result of this activity is that business actors in Sungkap Village understand the importance of recording their business finances to measure business performance and increase access to capital from financial institutions.